The Effects of Neurofeedback and Play Therapy on Dynamic Balance in 4-10 years old Children with Diplegic Spastic Cerebral Palsy - Emami Korande 1, Maryam; Barati 2, Amirhossein; Haghighi 3*, Mina; Peimani 4, Javid (Shahroud Journal of Medical Sciences, 2020)
Background: Dynamic balance is one of the most important challenges for kids who suffer from cerebral palsy especially diplegic spastic ones. Therefore, this study designed to compare the neurofeedback and play therapy training on dynamic balance in 4-10 years old diplegic spastic cerebral palsy kids.Methods: Quasi-experimental with three groups and pre-posttest design. This study has involved 26 spastic diplegia cerebral palsy children in 1st and 2nd grades, according to the GMFCS protocol. The researcher performed first, initial tests to evaluate the patient’s equilibrium level, by using the PBS assessment instruments. To investigate the study goals, the patients were divided into two groups with a two-study method of neurofeedback and play therapy. Each group has done their special exercises during 10 sessions in 2 weeks for the first group and 20 sessions in 4 weeks for the second time and finally, the PBS test was repeated. Primary data were analyzed using descriptive and argumentative statistics by Kolmogorov-Smirnov test, independent t-test, Wilcoxon test, and one-way and two-way ANOVA test. All of these analyzes were done by SPSS software.Results: The study’s results confirm that play therapy has shown a meaningful effect (Pvalue=0.042), while the effect of the neurofeedback method does not represent any legal effect on one’s dynamic balance. In the case of the dynamic balance, the play therapy group has shown better operation in post-tests compared with the neurofeedback group.Conclusions: As results show the play therapy method has shown a meaningful effect on dynamic balance so it has been suggested to improving elderlies balance.Keywords: Cerebral palsy, Neurofeedback, Play therapy, Statistic equivalent, Dynamic equivalent.